Media Strategies of Orthodox Church Television Networks: A Comparative Analysis of Romania, Serbia, Greece, Russia, and Georgia - Tsotniashvili , Zaza; Abuladze, Elizabeth (Journal of Digital Sociohumanities, 2025)
This study examines the media strategies employed by Orthodox Church television networks in five predominantly Orthodox countries: Romania, Serbia, Greece, Russia, and Georgia. As religious broadcasting continues to play a significant role in shaping public discourse and reinforcing religious identity, this research explores how these networks navigate the intersection of faith, culture, and media in their respective sociopolitical contexts. Through a comparative analysis, the article investigates the programming content, audience engagement tactics, and technological adaptations utilized by these networks, as well as their responses to challenges such as secularization, digital transformation, and political influences. By drawing on case studies from each country, the study highlights both commonalities and divergences in their media strategies, shedding light on the evolving role of religious media in the digital age. The findings contribute to broader discussions on the relationship between religion, media, and society, offering insights into how Orthodox Church televisions balance tradition and innovation to maintain relevance in a rapidly changing media landscape.